Role of Protein Tyrosine Phosphatases in Plants - Shankar, Alka; Agrawal, Nisha; Sharma, Manisha; Pandey, Amita; K. Pandey, Girdhar (Current Genomics, 2015)
Reversible protein phosphorylation is a crucial regulatory mechanism that controls many biological processes in eukaryotes. In plants, phosphorylation events primarily occur on serine (Ser) and threonine (Thr) residues, while in certain cases, it was also discovered on tyrosine (Tyr) residues. In contrary to plants, extensive reports on Tyr phosphorylation regulating a large numbers of biological processes exist in animals. Despite of such prodigious function in animals, Tyr phosphorylation is a least studied mechanism of protein regulation in plants. Recently, various chemical analytical procedures have strengthened the view that Tyr phosphorylation is equally prevalent in plants as in animals. However, regardless of Tyr phosphorylation events occuring in plants, no evidence could be found for the existence of gene encoding for Tyr phosphorylation i.e. the typical Tyr kinases. Various methodologies have suggested that plant responses to stress signals and developmental processes involved modifications in protein Tyr phosphorylation. Correspondingly, various reports have established the role of PTPs (Protein Tyrosine Phosphatases) in the dephosphorylation and inactivation of mitogen activated protein kinases (MAPKs) hence, in the regulation of MAPK signaling cascade. Besides this, many dual specificity protein phosphatases (DSPs) are also known to bind starch and regulate starch metabolism through reversible phosphorylation. Here, we are emphasizing the significant progress on protein Tyr phosphatases to understand the role of these enzymes in the regulation of post-translational modification in plant physiology and development.
Keywords: Protein tyrosine phosphatase